Perinatal Infection with Listeria monocytogenes: A 10-Year Hospital-Based Study in Western China - Zhan Y; Xu T; Liu H; Wang X; Yu H (Dove Medical Press, 2023)
Yongchi Zhan,1,2 Tingting Xu,1,2 Hongyan Liu,1,2 Xiaodong Wang,1,2 Haiyan Yu1,2 1Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of ChinaCorrespondence: Haiyan Yu; Xiaodong Wang, Department of Obstetrics and Gynecology, West China Second University Hospital; Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, No. 20, 3rd Section, South Renmin Road, Chengdu, Sichuan, 610041, People's Republic of China, Email fanjy422@163.com; wangxd_scu@sina.comObjective: Listeriosis is a rare but severe foodborne disease that is contracted by the consumption of food contaminated with Listeria, and perinatal listeriosis can cause major adverse pregnancy outcomes. In the current study, we sought to retrospectively analyze 10 years of perinatal outcomes due to listeriosis in western China.Methods: Based on the isolation of Listeria monocytogenes (L. monocytogenes), we retrospectively reviewed the pregnancy-associated cases of listeriosis from June 2010 to February 2022 at our hospital. We investigated the crude incidence, clinical manifestations, perinatal management, and outcomes of perinatal listeriosis cases.Results: We diagnosed a total of 28 cases of perinatal listeriosis during the study period at our hospital, including four cases of twin pregnancies. Of the 28 cases, 32.14% (9/28) were infected in the second trimester and 67.86% (19/28) in the third trimester. The fetal or neonatal mortality rate for perinatal listeriosis was high, with a crude fetal mortality rate of 46.88% (15/32) in the 32 offspring and a neonatal mortality rate of 47.06% (8/17) in the 17 live births.Conclusion: Perinatal listeriosis exhibits high fetal or neonatal mortality. We recommend that appropriate antibiotics be administered in cases of perinatal listeriosis.Keywords: Listeria monocytogenes, bacteremia, perinatal listeriosis, perinatal outcomes